PENGARUH RETURN ON EQUITY, CURRENT RATIO, UKURAN PERUSAHAAN TERHADAP DEBT TO EQUITY RATIO PADA PERUSAHAAN TRANSPORTASI YANG TERDAFTAR DI BURSA EFEK INDONESIA TAHUN 2014-2017 - Saputro, Muhammad Tri; Pratiwi, Permata Dian (Universitas Ahmad Dahlan, 2019)
The purpose of this study is to further investigate the effect of Return On Equity, Current Ratio, Company Size against Debt to Equity Ratio in the company transportation listed on the Indonesia Stock Exchange during the 2014-2017 period. That ratio used, namely Return On Equity, Current Ratio, Company Size and Debt to Equity Ratio. The method used is using panel data linear regression method. The population used in this study is a registered transportation company on the Indonesia Stock Exchange in the 2014-2017 period, published data and financial reports in full and have a positive net profit in the 2014-2017 period. Based on these criteria, the sample used in this study was 9 companies with population of 35 companies. The sampling technique uses a purposive technique sampling. Data were tested using a classic assumption test, panel data regression analysis, and test hypothesis. The results of this study indicate that Return On Equity, Current Ratio, Size The company has no significant effect on Debt to Equity Ratio.